2016
DOI: 10.1007/s10340-016-0790-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the surrounding landscape on the colonization rate of cereal aphids and phytovirus transmission in autumn

Abstract: International audienceEcological control has often focused on factorsenhancing control of pests by their natural enemies, whilefactors reducing the colonization rate of crops by pestshave been comparatively neglected. We present anapproach to assess landscape influence on the intensity ofwheat colonization by a major crop pest, the aphidRhopalosiphum padi. We used trays containing wheatseedlings to monitor field colonization by R. padi andbarley yellow dwarf viruses’ transmission in two areas inFrance in autum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Thus, the presence of winter cereal surfaces could lead to increased aphid abundances on maize because of a possible concentration effect (Root 1973) in early seasons at small landscape scales. This trend was also reported by Gilabert et al (2017), who showed that aphid populations increase in homogeneous landscapes dominated by cereals. Although the effect of non-crop habitats on the abundance of herbivorous insects has been found to be inconsistent (Chaplin-Kramer et al 2011), the proportion of non-crop habitats had a positive effect in this study on the early-season aphid abundance at the three scales.…”
Section: Effects Of Landscape and Field Variables On The Vectors Of Mdmv And Scmvsupporting
confidence: 84%
“…Thus, the presence of winter cereal surfaces could lead to increased aphid abundances on maize because of a possible concentration effect (Root 1973) in early seasons at small landscape scales. This trend was also reported by Gilabert et al (2017), who showed that aphid populations increase in homogeneous landscapes dominated by cereals. Although the effect of non-crop habitats on the abundance of herbivorous insects has been found to be inconsistent (Chaplin-Kramer et al 2011), the proportion of non-crop habitats had a positive effect in this study on the early-season aphid abundance at the three scales.…”
Section: Effects Of Landscape and Field Variables On The Vectors Of Mdmv And Scmvsupporting
confidence: 84%
“…One of the factors that influences aphid levels is landscape composition with more aphids occurring where there is uncropped land such as grassland, moorland, wasteland, while virus levels were lower where arable land dominates 14 . In contrast, a recent French study found that colonization was reduced when grassland cover in the landscape was high and increased when there was more maize in the surrounding 1 km radius circle 15 . Climate warming may lead to maize being grown further north across Europe.…”
Section: Introductionmentioning
confidence: 82%
“…) and sentinel seedlings (Gilabert et al . ) may be used to monitor population movements. To manually inspect grasses for D. noxia colonies, the base of leaves, particularly where they begin to wrap around the stem, should be checked, and flag leaves should be unwrapped from around emerging grass heads (particularly in the case of H. murinum , a highly preferred weed host).…”
Section: Managementmentioning
confidence: 99%